2018
DOI: 10.1080/13548506.2018.1475679
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout and work stress among Israeli dental assistants

Abstract: Professional burnout and work-related stress are known problems that have been the subject of in-depth examination among dentists. Nevertheless, these issues have not been widely studied among dental assistants. The aims of this study were threefold: to confirm the structure of a Work Stress Inventory (WSI) for Dental Assistants which was originally developed for Jordanian dental assistants (factor analysis); to evaluate work stress and burnout among Israeli dental assistants and to discover the factors predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Professional burnout in the medical professions is a well‐known problem and the subject of numerous studies. Studies demonstrate high levels of burnout among physicians, nurses, dentists, hygienists and dental assistants. The main risks quoted for burnout among dentists include work and time pressure, financial worries, difficult patients and problems with dental staff.…”
Section: Discussionmentioning
confidence: 99%
“…Professional burnout in the medical professions is a well‐known problem and the subject of numerous studies. Studies demonstrate high levels of burnout among physicians, nurses, dentists, hygienists and dental assistants. The main risks quoted for burnout among dentists include work and time pressure, financial worries, difficult patients and problems with dental staff.…”
Section: Discussionmentioning
confidence: 99%
“… 33 A study among DAs in Israel from 2019 found high levels of burnout among DAs and revealed that the most stressful work-related factors were, among others, the salary and work hazards. 34 Supposedly, both conditions have worsened for DAs in Germany during the pandemic and might contribute to the observation of high depression and anxiety levels in this study. Eventually, a study among Taiwanese dental staff found DAs to present the highest values for emotional exhaustion and depersonalisation compared with other dental staff.…”
Section: Discussionmentioning
confidence: 74%
“…The Crohn Bach alpha for each factor respectively came out to be 0.77 ,0.8 and 084 which was considered good compared to previous studies using the same scale. [14][15][16] as followed from previous literature burnout was identified at higher levels based on the following scoring system: Emotional exhaustion>14, cynicism> 6 and professional efficacy >23. The Jefferson Empathy Score, students version is a 20 item questionnaire rated on a 7-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…It composes of both negative and positive correlations. 15 Statistical analysis: was carried out on SPSS version 22.Descriptive statistics were applied on all demographic data, the MBI-SE items were evaluated using backward linear regression analysis, bivariate analysis to compare various descriptive with individual descriptive components, Chi square test was applied to see the impacts of gender, year of study and discipline of study on burnout. JSPE scores were reported as mean± standard deviation of each item, the evaluation of empathy with advancing years of study and different disciplines were evaluated using Analysis of variance (ANOVA) and independent t-test was employed to find out the difference in empathy between genders.…”
Section: Methodsmentioning
confidence: 99%